Evaluation of Gastroprotective Activity of Cemot Leaves (Passiflora foetida L.) Extracted by Ultrasonic Assisted Extraction (UAE) Against Ethanol-Induced Gastric Lesions in Rats - Elsa Trinovita; Fatmaria Fatmaria (Majalah Obat Tradisional, 2020)
Peptic ulcers are one of the global health problems in the world. However, most of these drugs have unwanted side effects and drug interactions that this research focuses on the use of plant products as an anti gastric ulcer. The phytochemical of Passiflora foetida L. leaves or better known by the name of the Central Borneo with 'Cemot' such as flavonoids, alkaloids, and tannin has potential as a gastroprotective. This study used the method of extraction of non-conventional, namely the UAE, because it has advantages compared with other conventional methods. This study aims to investigate the gastroprotective activities of ethanol extract of Passiflora foetida leaves-UAE. Cemot extract was obtained by UAE method using a concentration of ethanol (70%), the ratio of sample/liquid (10g/mL) for 3 minutes. Three groups of rats treated with a respective dose of the extract (50, 100 and 200 mg/kg BW), one group of rats treated with omeprazole 36 mg/kg BW for seven days before peptic ulcer induction using ethanol. The activity gastroprotective with measurement of lesion of gastric ulcer index and the percentage of inhibition ulcer. Group of rats treated with 200 mg/kg BW extract showed a decreased the ulcer index and ulcer inhibition than the other extract dosage groups, respectively 2.83 and 35.34%. Conclusion: Based on the results of this study concluded that the cemot extract has potential as a gastroprotective.